2011
DOI: 10.1163/138855410x518498
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphological characterisation of species within the Xiphinema americanum-group (Dorylaimida: Longidoridae) from the central valley of Chile

Abstract: Species of the Xiphinema americanum-group are among the most damaging nematodes for a diverse range of crops. This group includes 51 nominal species throughout the world. They are very difficult to identify by traditional taxonomic methods. Despite its importance in agriculture, the species composition of this group in many countries, including Chile, remains unknown. In order to identify the species in the central valley of Chile, we studied the morphological, morphometric and molecular diversity of 13 popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Sequences revealing high similarity to those obtained here were included in the phylogenetic analyses of both ribosomal and mitochondrial gene regions (Neilson et al 2004, Oliveira et al 2004, He et al 2005b, Gozel et al 2006, Holterman et al 2006; Lazarova et al 2006, Kumari et al 2009, Gutiérrez-Gutiérrez et al 2010, Kumari et al 2010a, Kumari et al 2010b, De Luca and Agostinelli 2011, Gutiérrez-Gutiérrez et al 2011a, Gutiérrez-Gutiérrez et al 2011b, Meza et al 2011, Sakai et al 2011, Gutiérrez-Gutiérrez et al 2012, Kumari and Subbotin 2012, Sakai et al 2012, Kumari and Cesare 2013, Tzortzakakis et al 2014, Getaneh et al 2015, etc). Sequence numbers are presented in the trees.…”
Section: Methodsmentioning
confidence: 95%
“…Sequences revealing high similarity to those obtained here were included in the phylogenetic analyses of both ribosomal and mitochondrial gene regions (Neilson et al 2004, Oliveira et al 2004, He et al 2005b, Gozel et al 2006, Holterman et al 2006; Lazarova et al 2006, Kumari et al 2009, Gutiérrez-Gutiérrez et al 2010, Kumari et al 2010a, Kumari et al 2010b, De Luca and Agostinelli 2011, Gutiérrez-Gutiérrez et al 2011a, Gutiérrez-Gutiérrez et al 2011b, Meza et al 2011, Sakai et al 2011, Gutiérrez-Gutiérrez et al 2012, Kumari and Subbotin 2012, Sakai et al 2012, Kumari and Cesare 2013, Tzortzakakis et al 2014, Getaneh et al 2015, etc). Sequence numbers are presented in the trees.…”
Section: Methodsmentioning
confidence: 95%
“…Consequently, currently available molecular techniques may help to provide tools for differentiating X. americanum ‐group species that could significantly improve and facilitate the routine identification of these nematodes. Polyphasic identification, based on an integrative strategy of combining molecular techniques with morphology and measurements for species diagnosis, has proved to be an efficient and reliable tool for nematode identification within this and other nematode groups (Derycke et al ., ; Meza, Aballay & Hinrichsen, ; Gutiérrez‐Gutiérrez et al ., , ). In Spain, the X. americanum ‐group was recently studied by Gutiérrez‐Gutiérrez et al .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, currently available molecular techniques may help to provide tools for differentiating X. americanum-group species that could significantly improve and facilitate the routine identification of these nematodes. Polyphasic identification, based on an integrative strategy of combining molecular techniques with morphology and measurements for species diagnosis, has proved to be an efficient and reliable tool for nematode identification within this and other nematode groups (Derycke et al, 2010;Meza, Aballay & Hinrichsen, 2011;Gutiérrez-Gutiérrez et al, 2012. In Spain, the X. americanum-group was recently studied by Gutiérrez-Gutiérrez et al (2010, 2012 on populations from grapevines and other host-plants in southern Spain, where two new species were described (Xiphinema parapachydermum and Xiphinema paratenuicutis), and four new records for the country were reported (Xiphinema duriense, X. incertum, X. opisthohysterum, Xiphinema santos).…”
Section: Introductionmentioning
confidence: 99%
“…The South African population is both morphometrically and genetically similar to X. peruvianum . Meza et al (2011) indicated that a high homology exists between Chile population of X. peruvianum and X. oxycaudatum identified from Taiwan. The South African population are similar to X. peruvianum but are distinguished by their shorter odontostyle and tail shape.…”
Section: Discussionmentioning
confidence: 94%